algebra

using the substitution method how do you solve y=-1/3x y+2x=5

  1. 👍
  2. 👎
  3. 👁
  1. y=(-1/3)x

    y+2x=5

    (-1/3)x+2x=5

    (-1/3)x+(6/3)x=5

    (5/3)x=5 Multiply with 3

    5x=15 Divide with 5

    x=15/5=3

    y=(-1/3)x

    y=(-1/3)*3= -1

    x= 3 y= -1

    1. 👍
    2. 👎

Respond to this Question

First Name

Your Response

Similar Questions

  1. Algebra PLEASE HELP!!

    What advantages does the method of substitution have over graphing for solving systems of equations? Choose the correct answer below. A. Graphing cannot be used to solve dependent or inconsistent systems due to the nature of the

  2. Math

    1. Explain the advantages and disadvantages of both the substitution method and the elimination method for solving a system. Help please. The only reasons I can think of is because in substitution it might be more difficult cause

  3. Pre-Calc

    Solve the system of equations using either the substitution method or the multiplication/addition method answer: 3x+2y=14 2x-4y=4

  4. Algebra

    If 2x + 2y = 20 & 5x - 3y = 15 Solve using the substitution method.

  1. algebra

    Solve the following system using the substitution method: 6x - 2y = -4 y = 3x + 2

  2. algebra

    Solve the given system by the substitution method. 3x + y = 17 5x -2y = 10

  3. algebra

    x+3y=-10 7x-5y=34 solve using substitution method

  4. 0303 math

    Solve the system by the substitution method y=-2x-4 5x-2y=-1

  1. Maths

    Solve 3x+y=25, xy=8 using substitution method

  2. algebra

    Solve the following system using the substitution method: 3x + y = -3 y = 2x + 7

  3. Mathematics

    X^2+y^2=34 X+Y=2(solve using substitution method)

  4. Substitution Method-Plz help

    Use the Substitution method to solve the system of equations. x + y = -4 x - y = 2 solve for x in the second equation. x= y+2 Put that in for x in the first equation: x+y=-4 (y+2) + y = -4 solve for y. Then, x= y+2 i don't get

You can view more similar questions or ask a new question.